Students’ Descriptive Text Writing in Experiential Function Realization - Sri Rahmadhani Siregar (English Education : English Journal for Teaching and Learning, 2021)
The main focus of the research was to know the students’ descriptive writing in experiential function realizations and to find out the dominant process in that problems. Qualitative research was used in conducting this research. The participants of this research were 26 students at TBI-1 seventh semester of English Department IAIN Padangsidimpuan. The instrument to collect the data was the documents of students’ answer sheet in writing descriptive text. The data were analyzed by using Cresswell’s theory these are organizing and preparing data, reading data, coding data, generating description of data, representing data, and interpreting data. The result showed that the students’ writing descriptive text in experiential function realized on six process. The processes were material, verbal, mental, relational, behavioral and existential process. From the six processes, relational process realization was the dominant on students’ sentences. There are 47.67%process was categorized into relational process.